Bosutinib Acts as a Tumor Inhibitor via Downregulating Src/NF‐κB/Survivin Expression in HeLa Cells. Issue 12 (9th October 2019) - Yu, Liang; Guo, Weiqiang; Liu, Ling; Zhang, Guoping; Zhang, Fahuang; Qu, Yuan; Liu, Yining; Li, Hui; Li, Huiwu
ABSTRACT: Efforts have been made to find effective medical drugs for cervical cancer treatment. The incidence of cervical cancer ranks second among women, and is a serious threat to women's health. Aberrant activation of the nonreceptor protein tyrosine kinases such as Src is commonly observed in progressive stages of human tumors. Thus, targeting Src kinase could be a promising strategy for cervical cancer therapy. In this study, we explored the potential utility of bosutinib in the treatment of cervical cancer. We found that bosutinib, as a potent dual Src/Abl inhibitor, could exert anti‐tumor effects on cervical cancer. Bosutinib inhibited cervical cancer cells proliferation and colony formation ability in a dose‐dependent manner, and also induced apoptosis. Mechanistically, bosutinib effectively decreased the activity of Src/NF‐κB/survivin signaling pathway. Our study provided a biological rationale to test bosutinib as a valuable therapeutic option for cervical cancer patients. Anat Rec, 302:2193–2200, 2019. © 2019 American Association for Anatomy